ダイ 26 ジ ナンキョク チイキ カンソク タイ キショウ ブモン ホウコク 1985 - 召田, 成美; メシダ, シゲミ; 福沢, 志津夫; フクサワ, シズオ; 島本, 高志; シマモト, タカシ; 若林, 正夫; ワカバヤシ, マサオ; Meshida, Shigemi; Fukusawa, Shizuo; Shimamoto, Takashi; Wakabayashi, Masao (1989)
P(論文) この報告は第26次南極地域観測隊越冬隊気象部門が, 1985年2月1日から1986年1月31日まで, 昭和基地において行った気象観測の結果をまとめたものである。観測項目・方法は第25次観測隊とほぼ同じであるが, 新たにサンフォトメータの観測を開始し, 高層気象観測用の気球充填ガスを全面的にヘリウムに切り替えて運用した。越冬期間中に特記される気象現象としては, 次のものがあげられる。1) オゾン全量観測において, 冬期間を除いた月平均値が過去最低を記録した。特に, 9,10月で低く, 1985年10月11日に観測された176(単位m atm-cm)は, 観測開始以来の最低値である。2) 100mbより上の成層圏気温年平均値は, 1981年より低下傾向が続いており, 過去最低を記録した。3) 基地周辺の海氷は3-5月にほとんど流失した。4) 7月16日に, みずほ基地において観測開始以来の最低気温-61.9℃を記録した。 This paper describes the results of meteorological observations at Syowa Station, from February 1,1985 to January 31,1986,carried out by Meteorological Observation Team of the 26th Japanese Antarctic Research Expedition. Observation items and methods are almost the same as in 1984. Newly, observation by sunphotometer has started, and helium gas was used for all aerological observation balloons instead of hydrogen gas. Remarkable characteristics are as follows : 1) In a period without winter, monthly means of total amount of ozone recorded the lowest values. Especially, the value was low in September and October, and 176 (m atm-cm) observed on October 11,1985 was the lowest since observation had started. 2) Annual mean temperature above 100-mb height in the stratosphere has been tending lower from 1981,and recorded the lowest value in 1985. 3) Sea ice around the Ongul Islands almost flowed away during March to May. 4) Minimum temperature of Mizuho Station, -61.9℃ (July 16,1985), was the lowest value since observation had started. departmental bulletin paper